Pengaruh Jumlah dan Posisi Pemasangan Guide Vanes Pada Elbow Ducting Terhadap Besarnya Pressure Drop - Mulawarman, A.A.N.B; Wijaya Kusuma, I Gusti Bagus (Jurnal Energi Dan Manufaktur, 2013)
Duct system is connecting between the refrigeration system and room to be conditioned. Room air streamed into the cooling coil through the return duct intake, air filters. Furthermore, the air sucked by the blower, which flowed into the evaporator. Through the register box, air conditioned which has flowed back into the room. When flowing inside the duct, the air has obstacle. One inhibiting factor is the change in direction of flow due to bends. That occurs at elbow is caused by friction (friction loss) and flow separation (separation loss). The aims of this research is to examine the phenomenon of the flow with Re = 3824 x 104 on a rectangular elbow as well as knowing how to influence the guide vanes at the elbow ducting channels. Based on data from research results, the number of guide vanes and position affects the pressure drop. From the graph shows that the installation of guide vanes to reduce pressure drop when fluid flows through the elbow. Installation guide vanes with the number five result in the smallest pressure drop of 9.1%. Efficiency caused by the installation of guide vanes reached 27.6%. Can be concluded that the installation of guide vanes on the elbow can be used as a reference in the design of ducting so as reduce the energy consumption.
Keywords: guide vanes, ducting, pressure drop